2018
DOI: 10.2134/agronj2018.02.0092
|View full text |Cite
|
Sign up to set email alerts
|

Soil Benefits and Yield Limitations of Cover Crop Use in Texas High Plains Cotton

Abstract: Core Ideas Soil organic C was two times greater with a no‐tillage rye cover crop system compared with conventional tillage (winter fallow) 17 yr after imposing treatments. A greater rate of C gain was observed with a no‐tillage mixed species cover crop system than with a rye cover crop in a 3‐yr period. Cotton lint yield and gross margins were less with a no‐tillage rye cover crop system than conventional tillage. Differences of lint yield and gross margins did not exist between the conventional tillage and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 42 publications
1
43
2
Order By: Relevance
“…The surface soil has a pH of 7.5 and is ∼70% sand (USDA‐NRCS, 2016). Additional information of initial soil characterization is described in Lewis et al (2018). In brief, conservation tillage was established in 1998 to compare monoculture cotton production using conventional tillage (CT)‐winter fallow and NT with cereal rye ( Secale cereale L.) cover.…”
Section: Methodsmentioning
confidence: 99%
“…The surface soil has a pH of 7.5 and is ∼70% sand (USDA‐NRCS, 2016). Additional information of initial soil characterization is described in Lewis et al (2018). In brief, conservation tillage was established in 1998 to compare monoculture cotton production using conventional tillage (CT)‐winter fallow and NT with cereal rye ( Secale cereale L.) cover.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reviewed the adoption of NT in the United States (Prokopy et al., ; Ranjan, Church, Floress, & Prokopy, ) and concluded that NT resulted in improvements in soil properties, greater cropping intensity, and higher crop productivity (Hansen, Allen, Baumhardt, & Lyon, ; Wallace et al., ). Agronomic and economic influences of cover crop adoption have been evaluated in studies of different cropping systems (Lewis et al., ; Schomberg et al., ; Zhou, Larson, Boyer, Roberts, & Tyler, ). The outcomes of these studies varied across regions and were affected by other farm practices, such as fertilizer application and crop rotation (Marcillo & Miguez, ; Miguez & Bollero, ; Ranjan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lewis et al. () evaluated the impact of conservation tillage and cover crops used in cotton production in north Texas, and found that cotton lint revenue and gross margins of CT were greater than conservation tillage. Based on a long‐term cotton experiment with various winter cover crops (wheat, hairy vetch [ Vicia villosa L.], and crimson clover [ Trifolium incarnatum L.]) and tillage treatments (till vs. NT) in Tennessee, Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oftentimes, conservation tillage and cover crops are adopted together to control input costs and augment environmental and economic benefits (Schomberg et al., 2014). Great efforts have been made to enhance soil health through conservation tillage and cover crop usage (Cochran, Roberts, Larson, & Tyler, 2007; Lewis et al., 2018). Compared to conventional tillage, conservation tillage, including no‐till and reduced tillage, reduces soil erosion, decreases input costs, and sustains long‐term farm productivity (Pittelkow et al., 2015).…”
Section: Introductionmentioning
confidence: 99%